Metropolitan Barcelona 2001–06, or How People’S Spatial–Temporal Behaviour Shapes Urban Structures - Cerda-Troncoso, J (Routledge, 2020)
Traditionally, urban structure has been analyzed using employment density or commuting. The main contribution of this paper is the use of a new source of information which includes other daily activities and that can be integrated into existing subcentre-identification methods. Thus, subcentres are identified using a time-density indicator departing from origin–destination surveys. Results suggest that changes in urban structure during the period under review have taken place in parallel to economic growth and that urban sprawl has increased in all activities except for healthcare and work, where the timeshare lost by the central business district has been redistributed to subcentres and peripheries. © 2019, © 2019 Regional Studies Association.